2023
DOI: 10.1136/bmjopen-2022-068071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the VivaSight double-lumen tube on the incidence of hypoxaemia during one-lung ventilation in patients undergoing thoracoscopic surgery: a study protocol for a prospective randomised controlled trial

Abstract: IntroductionA double-lumen tube (DLT) is a traditional one-lung ventilation tool that needs to be positioned under the guidance of a fibreoptic bronchoscope or auscultation. The placement is complex, and poor positioning often causes hypoxaemia. In recent years, VivaSight double-lumen tubes (v-DLTs) have been widely used in thoracic surgery. Because the tubes can be continuously observed during intubation and the operation, malposition can be corrected at any time. However, the effect of v-DLT on perioperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(48 reference statements)
1
1
0
Order By: Relevance
“…The incidence of conversion to intubation in NI-SV patients was 8.6% in this study, within the reported range of 2–10% [ 20 ]. Hypoxemia occurred in 8.6% of the I-MV patients in this study, similiar to the 10–30% reported in the literature [ 21 ], and the condition was corrected by repositioning the DLT or double-lung ventilation. Thus, a significant difference was observed in intraoperative airway intervention events between the two ventilation strategies.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of conversion to intubation in NI-SV patients was 8.6% in this study, within the reported range of 2–10% [ 20 ]. Hypoxemia occurred in 8.6% of the I-MV patients in this study, similiar to the 10–30% reported in the literature [ 21 ], and the condition was corrected by repositioning the DLT or double-lung ventilation. Thus, a significant difference was observed in intraoperative airway intervention events between the two ventilation strategies.…”
Section: Discussionsupporting
confidence: 87%
“…The surgery could be performed smoothly after adjusting the CPAP pressure to 4 cm H 2 O. Currently, most research on CPAP is conducted using a DLT; moreover, it has been concluded that a CPAP of 5 cm H 2 O can improve oxygenation 26 , 27 . Few studies have investigated the optimal CPAP administered by BB, with only a few case reports using a pressure of 5 cm H 2 O 28 , 29 ; therefore, we used a CPAP of 5 cm H 2 O in this study.…”
Section: Discussionmentioning
confidence: 99%